2015
DOI: 10.1504/ijtgm.2015.067972
|View full text |Cite
|
Sign up to set email alerts
|

Gravity model by panel data approach: empirical evidence from Nigeria

Abstract: Gravity trade model continue to be coveted for analysis of determinants trade flows among countries despite its lack of theoretical foundations. The main aim of the paper is to assess the determinants of flow of Nigeria's exports using longitudinal data from 1999 to 2012. Extrapolating from the empirical literature, the paper constructs Nigeria's gravity trade model comprising of 9 EU countries, BRICS countries, Canada, Japan and the US. Results from POOL and panel regressions-fixed and random effects show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
7
0
1
Order By: Relevance
“…The small number of R square are common for Random Effect Model estimation. Several studies resulted on R square only 57% [9], and 50% [10], and even there is other study that only shows R square of 48% [11]. Moreover, the results of F-test showed a P value of 0.0000 which is less than 0.05, which is can be concluded that all variables significantly influence the growth of Indonesia's palm oil exports (simultaneously).…”
Section: Resultsmentioning
confidence: 97%
“…The small number of R square are common for Random Effect Model estimation. Several studies resulted on R square only 57% [9], and 50% [10], and even there is other study that only shows R square of 48% [11]. Moreover, the results of F-test showed a P value of 0.0000 which is less than 0.05, which is can be concluded that all variables significantly influence the growth of Indonesia's palm oil exports (simultaneously).…”
Section: Resultsmentioning
confidence: 97%
“…To the best of the authors' knowledge, there is no significant research on Nigeria's cocoa exports using the gravity model. However, a limited number of studies are reported regarding the Nigerian trade (ALIYU & BAWA, 2015;OLADIPUPO & ADEDOYIN, 2019), cocoa exports competitiveness (NWACHUKWU et al, 2010) and political economy of cocoa (OLAIYA, 2016). It is thus apparent that there is a dearth of literature on the determinants of the Nigerian exports of cocoa.…”
Section: Abdullahi Et Almentioning
confidence: 99%
“…The outcome revealed a significant negative impact of FDI stock on bilateral trade development in Nigeria. A gravity model was applied by Aliyu and Bawa (2015) to assess Nigerian trade determinant but did not capture FDI and the method of analysis was restricted to ordinary least square (OLS) with fixed effect.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%